Aminoacylase I deficiency due to ACY1 mRNA exon skipping. (18th November 2013) - Ferri, L.; Funghini, S.; Fioravanti, A.; Biondi, E.G.; la Marca, G.; Guerrini, R.; Donati, M.A.; Morrone, A.
<x xml:space="preserve">Abstract</x> Aminoacylase 1 (ACY1) deficiency is a rare inborn error of metabolism of which less than 20 observations have been described. Patients exhibit urinary excretion of specific N‐acetyl amino acids and manifest a heterogeneous clinical spectrum including intellectual disability, motor delay, seizures, moderate to severe mental retardation, absent speech, growth delay, muscular hypotonia and autistic features. Here, we report the case of ACY1 enzyme deficiency in a 6‐year‐old girl presenting severe intellectual disability, motor retardation, absence of spontaneous locomotor activity and severe speech delay. Urinary excretion of N‐acetylated amino acids was present. Mutational analysis of ACY1 gene identified the new homozygous c.1001_1001+5del6 mutation, which alters the mRNA transcription leading to exon 13 skipping and inclusion of a premature stop codon (p.Lys308Glufs*7). A quantitative fluorescent multiplex‐polymerase chain reaction (QFM‐PCR) assay has been set up and confirmed homozygosity of the mutation in the patient's DNA. Biochemical analysis showed absence of ACY1 enzyme activity in the patient's fibroblasts. The structure of the mutated protein has been defined by homology modeling (HM). Our data endorse the hypothesis of a link between this inborn error of metabolism and the neurological manifestations observed in patients with ACY1 deficiency.